System analysis and modeling : languages, methods, and tools for systems engineering : 10th International Conference, SAM 2018, Copenhagen, Denmark, October 15-16, 2018, proceedings /: languages, methods, and tools for systems engineering : 10th International Conference, SAM 2018, Copenhagen, Denmark, October 15-16, 2018, proceedings. (2018) - Unknown
No abstract available